GABAergic interneuron diversity and organization are crucial for the generation of human-specific functional neural networks in cerebral organoids - Heesen, Sebastian H.; Koehr, Georg (Frontiers in neuroscience, 2024)
This mini review inves'gates the importance of GABAergic interneurons for the network func'on of human-induced pluripotent stem cells (hiPSC)-derived brain organoids. The presented evidence suggests that the abundance, diversity and three-dimensional cor'cal organiza'on of GABAergic interneurons are the primary elements responsible for the crea'on of synchronous neuronal firing paferns. Without intricate inhibi'on, coupled oscillatory paferns cannot reach a sufficient complexity to transfer spa'otemporal informa'on cons'tu'ng physiological network func'on. Furthermore, human-specific brain network func'on seems to be mediated by a more complex and interconnected inhibitory structure that remains developmentally flexible for a longer period when compared to rodents. This suggests that several characteris'cs of human brain networks cannot be captured by rodent models, emphasizing the need for model systems like organoids that adequately mimic physiological human brain func'on in vitro.
Gesehen am 28.05.2024